MS0621, a novel small-molecule modulator of Ewing sarcoma chromatin accessibility, interacts with an RNA-associated macromolecular complex and influences RNA splicing - Vital, Tamara; Wali, Aminah; Butler, Kyle V.; Xiong, Yan; Foster, Joseph P.; Marcel, Shelsa S.; McFadden, Andrew W.; Nguyen, Valerie U.; Bailey, Benton M.; Lamb, Kelsey N.; James, Lindsey I.; Frye, Stephen V.; et al. (Frontiers in Oncology, 2023)
Ewing sarcoma is a cancer of children and young adults characterized by the critical translocation-associated fusion oncoprotein EWS::FLI. EWS::FLI targets characteristic genetic loci where it mediates aberrant chromatin and the establishment of de novo enhancers. Ewing sarcoma thus provides a model to interrogate mechanisms underlying chromatin dysregulation in tumorigenesis. Previously, we developed a high-throughput chromatin-based screening platform based on the de novo enhancers and demonstrated its utility in identifying small molecules capable of altering chromatin accessibility. Here, we report the identification of MS0621, a molecule with previously uncharacterized mechanism of action, as a small molecule modulator of chromatin state at sites of aberrant chromatin accessibility at EWS::FLI-bound loci. MS0621 suppresses cellular proliferation of Ewing sarcoma cell lines by cell cycle arrest. Proteomic studies demonstrate that MS0621 associates with EWS::FLI, RNA binding and splicing proteins, as well as chromatin regulatory proteins. Surprisingly, interactions with chromatin and many RNA-binding proteins, including EWS::FLI and its known interactors, were RNA-independent. Our findings suggest that MS0621 affects EWS::FLI-mediated chromatin activity by interacting with and altering the activity of RNA splicing machinery and chromatin modulating factors. Genetic modulation of these proteins similarly inhibits proliferation and alters chromatin in Ewing sarcoma cells. The use of an oncogene-associated chromatin signature as a target allows for a direct approach to screen for unrecognized modulators of epigenetic machinery and provides a framework for using chromatin-based assays for future therapeutic discovery efforts.